Judicial review, ouster clauses, and the democratic credentials of the judiciary in the United Kingdom - Trueblood, LC (Cambridge University Press, 2025)
The aim of this paper is to challenge an argument that goes like this: judges are not elected; therefore, they have weaker or no democratic legitimacy as opposed to legislators. This article draws on dicta from Laws LJ, as he then was, in the Divisional Court case of Cart v Upper Tribunal to offer two reasons why this is false. Call these the efficacy and equality principles of representation. The claim here is that without an independent judiciary, legislators cannot legislate or legislate in a way that applies equally. So, without an independent judiciary, the democratic legitimacy of a legislature is weakened or disappears. This argument makes a legal difference, but the kind of legal difference it makes varies between jurisdictions. This paper focuses on one difference the democratic legitimacy of judges makes in the United Kingdom: the extent to which Parliament can oust judicial review for error of jurisdiction.